2013
DOI: 10.1186/cc12855
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for resuscitation of severe burn patients guided by transpulmonary thermodilution and lactate levels: a 3-year prospective cohort study

Abstract: IntroductionThe use of urinary output and vital signs to guide initial burn resuscitation may lead to suboptimal resuscitation. Invasive hemodynamic monitoring may result in over-resuscitation. This study aimed to evaluate the results of a goal-directed burn resuscitation protocol that used standard measures of mean arterial pressure (MAP) and urine output, plus transpulmonary thermodilution (TPTD) and lactate levels to adjust fluid therapy to achieve a minimum level of preload to allow for sufficient vital or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 34 publications
(43 reference statements)
0
42
0
Order By: Relevance
“…A lactate optimization strategy, as well as targeting CI, ITBV, EVLW and MAP in burn patients, was shown to avoid unnecessary fluid administration and provide adequate tissue perfusion at the same time [57].…”
Section: Continuous Lactate Monitoringmentioning
confidence: 99%
“…A lactate optimization strategy, as well as targeting CI, ITBV, EVLW and MAP in burn patients, was shown to avoid unnecessary fluid administration and provide adequate tissue perfusion at the same time [57].…”
Section: Continuous Lactate Monitoringmentioning
confidence: 99%
“…Considering the large variability of biometric parameters such as body weight (BW) and height volumetric parameters are usually adjusted for these biometric variables to improve inter-individual comparisons and to allow for homogenous normal ranges. GEDV indexed to body surface area (BSA) is termed GEDVI and has been demonstrated to be useful in assessing preload and to guide fluid therapy in several studies [1][2][3][4][5][6][7]. Nevertheless, some studies using algorithms based on GEDVI have failed to improve outcome [8,9].…”
Section: Introductionmentioning
confidence: 97%
“…Numerous studies have shown that these volumetric indices represent preload more precisely when compared to urine output [30,31] or cardiac filling pressures [50,53], which are prone to missing hypervolemia as it is poorly represented by the blood pressure, filling pressure and/or urine output in the early resuscitative phase [31]. By measuring the ejection fraction to correct these volumetric preload parameters, the ability of these parameters to assess changes in preload over time can be further improved [53].…”
Section: Volumetric Preloadmentioning
confidence: 99%
“…This consists of the interstitial, intracellular and intra-alveolar water of lung tissue. This parameter, together with the pulmonary vascular permeability index (PVPI), can be used to determine the presence of lung edema which can be very useful as a safety parameter during resuscitation [31]. This is particularly applicable in patients with inhalation injuries or in guiding fluid de-resuscitation if a patient fails to proceed to the "flow" phase [1−3].…”
Section: Volumetric Preloadmentioning
confidence: 99%